Improved Estimation of Glacial‐Earthquake Size Through New Modeling of the Seismic Source - Tavi Murray (Journal of Geophysical Research: Earth Surface, 2021)
The number of gigaton-sized iceberg-calving events occurring annually at Greenland glaciers is increasing, part of a larger trend of accelerating mass loss from the Greenland Ice Sheet. Though visual observation of large calving events is rare, ∼60 glacial earthquakes generated by these calving events are currently recorded each year by regional and global seismic stations. An empirical relationship between iceberg size and MCSF, a summary measure of glacial-earthquake size, was recently demonstrated by Olsen and Nettles (2019). However, MCSF is known to be sensitive to choices made in modeling the seismic source. We incorporate constraints on the seismic source from laboratory studies of calving and test multiple source time functions using synthetic and observed glacial-earthquake waveforms. We find that a simple, fixed time function with a shape informed by laboratory results greatly improves estimates of earthquake size. The average ratio of estimated to true peak force values is 1.03 for experiments using our preferred source model, compared with an average of 0.3 for models used in previous studies. We find that maximum-force values estimated from waveform modeling depend far less on model choices than does MCSF, and therefore prefer maximum force as a measure of glacial-earthquake size. Using both synthetic and real data, we confirm a correlation between maximum force and iceberg mass. Our results support the possibility of developing useful scaling relationships between seismic observables and physical parameters controlling glacier calving.